Doing theology with children in a South African context: Children as collaborators in intergenerational ministry - Weber, Shantelle (HTS teologiese studies, 2016)
The vision of Child Theology Africa is to advance a child-friendly continent by doing theology with, for, about and through African children. In this article we would like to explore the voice, role and position of the child in church and society, as important and integral to authentic intergenerational church praxis. This is based on the presuppositions that children should be regarded as collaborators in doing theology; children should be engaged not merely as objects but as subjects of research and knowledge generation; children articulate their own experiences with God; and the biblical imperatives to listen carefully to and engage with children.